Mathematical model of hospital length of stay - Le, Truc Viet. (2009)
Hospital length of stay (LOS) is often used as a reliable proxy for measuring the consumption of hospital resources. However, the empirical distribution of LOS is established to be highly skewed with a heavy right tail. This makes the applications of simple statistics, such as averaging, to LOS for measuring and planning of hospital resources unrealistic.